Cluster Approach to the Development of Youth Entrepreneurship in Classical University - V. Y. Stromov; P. V. Sysoyev; V. V. Zav’yalov (Высшее образование в России)
Training of qualified personnel in the field of entrepreneurship is one of the conditions for economic growth in the country. Modern universities which are centers of regional innovation development set themselves the task of creating competences in the field of entrepreneurship among students. The development of competences in the field of entrepreneurship among students of all other areas of training and specialties can significantly expand the employment opportunities for students upon graduation from the university and diversify small and medium-sized businesses in the regions. This paper presents the experience of Derzhavin Tambov State University on the implementation of the educational project “Youth Entrepreneurship”, focused on teaching entrepreneurship to students of all areas of training. The project was initiated and carried out by the joint student scientific council within the framework of the institute of mentoring, as well as in cooperation with the business structures of the region. The project based on the cluster approach includes five stages: 1) the joint student scientific council program; 2) the Tambov Innovation Business Incubator program; 3) “Geometry of business” program of the center of small and medium business support; 4) start-up development, and 5) opening of small innovative enterprises. The work presents in detail the substantive content of the project and describes its stages.